A study of histopathological spectrum and expression of Ki-67, TP53 in primary brain tumors of pediatric age group - Sengupta, Subhalakshmi; Chatterjee, Uttara; Banerjee, Uma; Ghosh, Samarendranath; Chatterjee, Sandip; Ghosh, Ashit K (Indian Journal of Medical and Paediatric Oncology, 2012)
Objectives: The primary brain tumors are the second most common cause of death due to malignancies in children. This study was done to analyze the histological spectrum of primary brain tumors in children and also to find out the expression of p53 and Ki67 in some of the common pediatric brain tumors. Materials and Methods: This study was done over a period of 2.5 years. The patients were followed up until 6 months to determine the outcome. We examined H and E sections from 61 pediatric brain tumors and also performed immunohistochemical stains with p53 and Ki67 on 52 of these samples. Results: Of the 61 cases of pediatric brain tumors the commonest were pilocytic astrocytomas and medulloblastomas both constituting 22.9% of total cases, followed by high grade gliomas, that is, anaplastic astrocytoma and glioblastoma taken together (14.7%), diffuse astrocytomas (11.4%), ependymomas (8.1%), and oligodendrogliomas (4.9%). Other cases comprised craniopharyngiomas, astroblastomas, and gangliocytoma. The mean age of presentation was 9.3 years, male children being more commonly affected. Ki67 labeling index (LI) and p53 expression in pilocytic astrocytomas and diffuse astrocytomas were significantly lower than that of high-grade astrocytomas. However, there was no significant difference of expression of these two antigens in pilocytic astrocytomas and diffuse astrocytomas. It was found that Ki67 LI was a better marker for distinguishing between grades of astrocytoma than p53 (P=0.000 and P=0.002, respectively). The survival in cases of pilocytic astrocytomas was far better than high-grade gliomas. However, there was no significant difference in survival between pilocytic astrocytoma and diffuse infiltrating astrocytoma. There was significant positive correlation between expression of p53 and Ki67 LI in cases of medulloblastomas. Both p53 (P=0.002) and Ki67 LI (P=0.000) taken individually correlated well with survival in these cases. Also, Ki67 LI is better predictor of outcome than p53. Conclusion: From this study, it can be concluded that Ki67 and p53 score correlated well with the grade of astrocytoma; however, Ki67 is a better marker for differentiating between the grades of astrocytoma than p53. Also, Ki67 LI is a better prognostic factor than p53 in case of medulloblastomas.
Keywords: Pediatric brain tumors; p53; Ki67